QSAR Studies of Benzylidene-9(10H) Anthracenone Derivatives: Tubulin Inhibitor in Cancer Therapy - PRAKASH B.N GUPTA, SURYA; HARI NARAYANA MOORTHY, N.S. (Asian Journal of Chemistry, 2010)
Stepwise multiple regression analysis was performed to find out the correlation between various physicochemical descriptors and biological activity of the compounds by using Openstat 2 version 6.5.1 and Valstat statistical software. Out of the several equations developed, the best equations having the highest significance were selected for further studies, which are mentioned below. -log IC50 = 0.396R2(±0.129) + 0.333R4(±0.212) + 0.236HD(±0.1 05)-0.273(±0.176) n = 17; r = 0.746; r2 = 0.556; F == 5.103 (1) -log IC50 == 0.273R2(±0.179) + 0.408HD(±0.239) + 0.186π(±0.069)-0.624(±0.234) n = 17; r = 0.615; r2 = 0.378; F = 4.641 (2) The results obtained from QSAR studies indicate that in both the equations, the HD, π and indicator variables R2 and R4contributed positively to the biological activity. In eqn. (1), the indicator variables at R2 and R4 position of the parent nucleus positively contribute to the activity. But in eqn. (2), R2, HD and π contribute positively. Both the equations have 85% significance and the F values are F = 5.103 and F = 4.641, respectively suggesting that the equations have very good predictive power.